2022
DOI: 10.3390/healthcare10020294
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Chuna Manipulation Therapy in 289,953 Patients with Musculoskeletal Disorders: A Retrospective Study

Abstract: Studies have reported that mild adverse events (AEs) are common after manual therapy and that there is a risk of serious injury. We aimed to assess the safety of Chuna manipulation therapy (CMT), a traditional manual Korean therapy, by analysing AEs in patients who underwent this treatment. Patients who received at least one session of CMT between December 2009 and March 2019 at 14 Korean medicine hospitals were included. Electronic patient charts and internal audit data obtained from situation report logs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…A rib fracture is also a recognized cause for malpractice litigation claims against chiropractors and, in one study, accounted for two of 48 claims in the United States (i.e., 4.2%) 46 . In the current study, the incidence of rib fractures was comparable to that identified in a previous study examining Chuna manipulation (i.e., 0.41; 95% CI 0.21, 0.70) 5 . However, in the current study, both cases of rib fracture were recorded as grade 3 (severe) AEs, whereas in the previous study, they were recorded as grade 2.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A rib fracture is also a recognized cause for malpractice litigation claims against chiropractors and, in one study, accounted for two of 48 claims in the United States (i.e., 4.2%) 46 . In the current study, the incidence of rib fractures was comparable to that identified in a previous study examining Chuna manipulation (i.e., 0.41; 95% CI 0.21, 0.70) 5 . However, in the current study, both cases of rib fracture were recorded as grade 3 (severe) AEs, whereas in the previous study, they were recorded as grade 2.…”
Section: Discussionsupporting
confidence: 86%
“…A sample size of 7,299 for our primary objective was calculated using data from a similar study that identified 50 AEs per 2,682,258 manipulations, yielding an incidence of 0.000019 for AEs 5 . The formula n = [Z2P(1 − P)]/(d2) was utilized wherein Z equals the Z statistic for the level of confidence of 95% (i.e., 1.96), P is the probability of 0.000019, and d is the required precision, of 0.0001 or 0.01% 39 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations